Policy Learning for Generating Green Electricity - Shahrabi, Narges Salehi; Bressers, J. T. A.; Garcia, M. L. Franco; Pourezzat, Ali Asghar (International Journal of Energy Economics and Policy, 2020)
An important challenge for any developing country is to achieve their green energy targets for clean electricity generation. In this respect, Iran is no exception. This paper sets out a reference point for Iran as a less developed country by learning the green electricity production policies from developed countries; Germany and Denmark. We used a mixed research approach. The most significant lessons learnt includes the relevance of the financial and regulatory tools and policies that have been successfully applied in Denmark and Germany. Our findings show the structure of fuel allocation to energy generation plants needs reforming. The result shows a considerable difference between Iran and the two other developed countries regarding the level of utilizing fossil fuels and renewable energies. We identified a wide range of beneficial measures to facilitate the transition to green energy production. These included: reforms to electricity pricing, phasing out nuclear energy production; the setting of a green tax package, subsidising renewable energy development for new and old systems, dedicating soft-interest loans, implementing informative programmes about local ownership, facilitating the process of participation, and performing obligatory plans to purchase green electricity for governmental sectors. Keywords: Policy instruments, Financial incentives, Regulatory incentives, Green Electricity, Renewable resources. JEL Classifications: Q28, Q48, K32 DOI: https://doi.org/10.32479/ijeep.10306